2010
DOI: 10.5020/18061230.2010.p43
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento sexual de mulheres com papiloma vírus humano em serviços de referência de Fortaleza, Ceará

Abstract: Sexual behavior of women with human papillomavirus in reference services of Fortaleza, Ceará RESUMOObjetivo: Analisar o comportamento sexual de mulheres com papiloma vírus humano (HPV) atendidas em duas unidades de referência para doenças sexualmente transmissíveis (DST) do município de Fortaleza-Ce. Métodos: Estudo quantitativo, descritivo, realizado nos meses de agosto a setembro de 2005, em duas unidades de referência para DST. Aplicou-se um questionário a todas as mulheres que estavam em tratamento para HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 10 publications
2
7
1
4
Order By: Relevance
“…This finding is supported by several studies that found a strong correlation between HPV infection and cytological anomalies (12,22) .…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This finding is supported by several studies that found a strong correlation between HPV infection and cytological anomalies (12,22) .…”
Section: Discussionsupporting
confidence: 79%
“…The frequency data were not significantly different in the bivariate analysis of the results of the preventive Pap tests. This finding is not consistent with previous studies in which there was a significant correlation between sexual behavior and HPV infection (6,7,11,12) and infection with multiple HPV types (13) .…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations